An efficient confinement strategy with CFRP sheets to increase the energy absorption capacity of RC concrete columns - Barros, Joaquim A. O. (2005)
The present work evidences the performances of distinct partial and full confinement CFRP systems, in terms of increasing the load carrying capacity and energy absorption capacity of reinforced concrete column elements. The influence of the strip’s width, the number of CFRP layers per strip and the stiffness of the CFRP sheet for these properties, is assessed. The experimental program is described and the main results are presented and analyzed.